(untitled) (Journal of Atomic and Molecular Sciences, 2014)
The uniform electron gas placed between two reservoirs is used as a model system for molecular junctions under an external bias. The energetics of the electron gas are calculated by generalizing the Thomas-Fermi-Dirac (TFD) model to nonequilibrium cases. We show that when the bias voltage is not zero, the first Hohenberg-Kohn (HK) theorem breaks down, and energies of the electron gas can be determined by the total electron density together with the density of nonequilibrium electrons, supporting the dual-mean-field (DMF) theory recently proposed by us [J. Chem. Phys. 139, (2013) 191103]. The generalization of TFD functionals to DMF ones is also discussed.